2016
DOI: 10.9734/ijtdh/2016/27280
|View full text |Cite
|
Sign up to set email alerts
|

Babesiosis and Other Heamoparasitic Disease in a Cattle Slaughtering Abattoir in Abeokuta, Nigeria

Abstract: Babesiosis, an haemoparasitic disease caused by Babesia spp and transmitted by ticks is one of the major public health threat to cattle rearing in most countries, including Nigeria. The disease impose a serious burden on the healthcare infrastructure of both the cattle and their handlers. This study therefore investigated the prevalence of Babesiosis and other haemoparasitic disease in a cattle slaughtering abattoir in Abeokuta, Ogun State, Nigeria. A total of 162 cattle were examined between May and August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
5
4
Order By: Relevance
“…The parasites cause various disease condition in cattle, ranging from anaemia, weight loss, jaundice to infertility thereby reducing the protein and economic value of the animals. The high prevalence (62.5%) of tick-borne haemoparasites recorded in this study is higher than the 57.1% and 27.8% reported by [19] and [20] in Abeokuta, Ogun state and 16% recorded by [9] in North Central Nigeria. The result obtained in this study is also higher than the 13.5% reported in Maiduguri by [21].…”
Section: Discussioncontrasting
confidence: 72%
“…The parasites cause various disease condition in cattle, ranging from anaemia, weight loss, jaundice to infertility thereby reducing the protein and economic value of the animals. The high prevalence (62.5%) of tick-borne haemoparasites recorded in this study is higher than the 57.1% and 27.8% reported by [19] and [20] in Abeokuta, Ogun state and 16% recorded by [9] in North Central Nigeria. The result obtained in this study is also higher than the 13.5% reported in Maiduguri by [21].…”
Section: Discussioncontrasting
confidence: 72%
“…Babesia species and Anaplasma species has been reported to be the most prevalent haemoparasites of small ruminants (sheep and goat) in northern Nigeria (Opara et al, 2016;Bello et al, 2017), southeastern Nigeria (Nwoha et al, 2013b;Ukwueze and Kalu 2015) and southwestern Nigeria (Akande et al, 2010;Sam-Wobo et al, 2016). Trypanosoma species were not detected from our study and this has been reported to be endemic among sheep and goats in southwestern Nigeria (Akande et al, 2010;Ademola and Onyiche, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, ruminants comprising sheep, goats and cattle constitute the livestock farm animals and about 36.4 58.0 million goats and 16.8 million cattle are currently been reared by farm families in the 2016). Of the ruminant livestock, cattle are regarded as the main source of animal protein in most household, and their products such as milk, hoof, bones, blood, hides and skin are also of economic benefits (Sam-Wobo et al, 2016) Dogs are believed to be the first domestic animal in most parts of the world (Kamani et al are important household pets mostly kept for various other reasons which include security purposes (personal and military), sheep herding and protection against predators, hunting and leading of the blind. Nigeria, there has been increased interest of dogs for security and or hunting or pets and for Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ruminants, cattle are regarded as the main source of animal protein in most household and their products such as milk, hoof, bones, blood, hides and skin have great economic bene ts (Sam-wobo et al 2016). 90% of the cattle population in Nigeria are raised under the pastoral husbandry system of Fulani herders (Musa et al 2014).…”
Section: Introductionmentioning
confidence: 99%